The Correlation between Cryptocurrency, Stock Prices, and Return on Assets of Tobacco Companies - Roza, Seflidiana; Nurhayati, Nurhayati; Maidari, Elfi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the relationship between cryptocurrency prices and stock prices as well as the return on assets of companies in the tobacco industry sub-sector listed on the Indonesia Stock Exchange (IDX) during 2022–2023. The research population consisted of four companies, all of which were included as samples. The data collected were divided into two categories: 96 data points for stock prices and 32 data points for return on assets. The analysis method used was simple linear regression. The results showed that cryptocurrency prices had no significant effect on either stock prices or the return on assets of the companies. The coefficient of determination (R²) indicated a very weak relationship: 0.01 for stock prices and 0.02 for return on assets. These findings suggest that cryptocurrency price fluctuations did not have a meaningful impact on stock performance or company profitability in this sub-sector during the observed period.